Innovating Public Service: The System Thinking Approach - Khanal, Rajan; Pokharel, Trilochan (Prashasan: The Nepalese Journal of Public Administration, 2022)
Public services are the product of the state to safeguard citizens’ entitlements, delivered either directly by the public sector or provisioned through other entities. The challenges for maintaining quality in public services are multifaceted, demanding a holistic approach for innovation. Nepal, an emerging economy, is struggling to institutionalize the political transformation enshrined through the Constitution of Nepal 2015. The Constitution has recognized the quality of public services as the fundamental rights of the people and the state is obliged to deliver it. The changing landscape with the advancement in science and technology, people’s knowledge, diversity and expansion of the public services, it is apparent to adopt innovative approaches to improve overall quality of the services that public sector delivers. Without an open thinking and applying ideas like system thinking and design thinking in the public service reform, it will be a daunting challenge for the government to meet the public expectations of quality services. This article presents the idea of innovating public services through the system and design thinking citing examples from Nepal’s public sector. Drawing a base from Bason’s Leading Public Sector Innovation: Co-creating for a Better Society, this article offers framework for innovation in Nepal’s public sector.